1996
DOI: 10.1063/1.360894
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index change in Al+-ion-implanted silica glass

Abstract: Al+ ions have been implanted in silica glass at an acceleration energy of 200 eV and doses ranging from 1×1013 to 1×1017 ions cm−2. Infrared reflection spectra and ultraviolet, visible, and near-infrared absorption spectra have been measured. It was found that refractive index of silica glass increased by 6%–10% after implantation of 1×1017 Al+ ions cm−2. It was deduced that this refractive index change is caused by the formation of Si—Si homobonds, but not by the decrease in Si—O—-Si bond angle which leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…There are several studies that found evidence for the predominance of this coordination state in low-alumina aluminosilicate glasses. For example, Al ions implanted into silica glass (1 × 10 15 –1 × 10 17 Al + ions cm 2 ) were found to simply substitute on Si-positions 27 . Nuclear magnetic resonance (NMR) and extended X-ray absorption fine structure (EXAFS) have shown that for ≤ 0.4 mol% of Al 2 O 3 , the Al ions are predominantly four-fold coordinated 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies that found evidence for the predominance of this coordination state in low-alumina aluminosilicate glasses. For example, Al ions implanted into silica glass (1 × 10 15 –1 × 10 17 Al + ions cm 2 ) were found to simply substitute on Si-positions 27 . Nuclear magnetic resonance (NMR) and extended X-ray absorption fine structure (EXAFS) have shown that for ≤ 0.4 mol% of Al 2 O 3 , the Al ions are predominantly four-fold coordinated 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] Also Al ions implanted in silica were found to occupy substitutional positions, pushing Si atoms into the interstitial region. [8][9][10][11] However, the state of fully oxidized Al impurities ͑that is, Al 2 O 3 units͒ in a silica network free of other impurities is still an open question. Brower 12,13 found EPR evidence of three-coordinated Al ions in silica fused from natural quartz with low alkali content, but a recent EXAFS 14 study of glass with an Al 2 O 3 concentration of ϳ0.4 mole % ͑compared to the ϳ10-100 ppm weight Al concentration in natural quartz͒ found only evidence of fourcoordinated Al species.…”
Section: Introductionmentioning
confidence: 99%
“…For Al-implanted silica glass, it has been found 8,11 that the implanted Al atoms are O coordinated for all implantation doses, and that this behavior persists during heat treatments, with no signs of cluster formation. For large implantation doses, Si-Si bonds were seen to form, presumably arising from bonding between the Si atoms that are pushed into the interstitial region.…”
mentioning
confidence: 99%
“…A number of experimental investigations have been performed in order to clarify the properties of Al and P impurities in both crystalline and amorphous silica, [1][2][3][4][5][6][7][8][9][10][11] but most of the results obtained are of a qualitative nature. The purpose of the present paper is to complement the experimental information by a theoretical study of the local chemistry governing the behavior of dilute Al or P impurities in a silica environment.…”
mentioning
confidence: 99%